A model-based measurement method for intelligent circuit breaker with data communication. (April 2018) - Liu, Zhiheng; Duan, Xiongying; Liao, Minfu; Ge, Guowei; Zou, Jiyan
In this paper, an object-oriented information model of an intelligent vacuum circuit breaker based on its physical structure and function (service) was established to integrate the measuring information flow of field parameters, the monitoring information flow of status data, and the operating and controlling information flow. The status parameters of the intelligent vacuum breaker were detected by analysing the principles and methods based on IEC61850 and IEC62271 standards. The IEC 61850 standard repository can be extended according to the characteristics of the intelligent vacuum breaker status parameters, and the IED server model was constructed to be suitable for the vacuum breaker. A key feature of the new method is the use of a multimode fibre that is incorporated into the IED server model to transmit the status parameters from the target to the sensor. The main characteristic of the measurement method is that it exhibits real-time transmission of data collection. The model includes temperature testing of the switch contact, vacuum arc testing, detection of vacuum switch motion and primary circuit parameters testing. Furthermore, we show how the IEC61850 standard can be used to give a better insight on data communication of the data collector and intelligent circuit breaker. Experimental results showed that the feasibility of intelligent vacuum breaker status monitoring through the switching-on test. It purposes to achieve information integration and a frame communication platform for the intelligent vacuum breaker.